The effects of the goalkeeper substitution rule as a new strategy in handball: Analysis of Men's European Handball Championship 2020 - Gümüs, H.; Gençoglu, C. (Acta Gymnica, 2020)
Background: The numerical inferiority in attacking due to the 2-min penalty is a disadvantageous situation in handball. Teams substitute the goalkeeper with a field player to tolerate this handicap. The rule change enabled the simple practicality of playing with an extra player and an empty net.